Augmented Reality in the Internet of Things (AR + IoT): A Review - Aulia Akhrian Syahidi; Kohei Arai; Herman Tolle; Ahmad Afif Supianto; Kiyoshi Kiyokawa (The IJICS (International Journal of Informatics and Computer Science), 2021)
Augmented Reality (AR) and Internet of Things (IoT) devices can converge, we call it AR + IoT. The integration of AR and IoT has promising opportunities for future product research and development. IoT is a tool for communicating, monitoring, and remotely controlling with connected products, while AR is a means to see and find out what is happening with connected products based on visualization/interface based on additional information. The mapping review method was used to carry out this research. The result is that as many as 43 papers from 2014-2020 are the main targets of review. The largest publication database is in the IEEE Xplore Digital Library, the application dominates in the field of social life, the research objectives are varied, and the recommended future work is to maximize the potential for integration between AR and IoT or even with other promising devices. Then comfort, convenience, and user experience are also recommended in implementing AR + IoT